2015
DOI: 10.1002/micr.22378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripheral microcirculation improvement of foot after tarsal tunnel release in diabetic patients by transcutaneous oximetry

Abstract: The results of postoperative increase in PtcO2 values demonstrate that the release of the tarsal tunnel determines a relevant increase in microcirculation in the feet of diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 20 publications
2
33
0
1
Order By: Relevance
“…Therefore, US‐guided tarsal tunnel release is feasible, as the surgeon can visualize the main structures involved. The goal of this study was to investigate the efficacy and safety of US‐guided tarsal tunnel release …”
mentioning
confidence: 99%
“…Therefore, US‐guided tarsal tunnel release is feasible, as the surgeon can visualize the main structures involved. The goal of this study was to investigate the efficacy and safety of US‐guided tarsal tunnel release …”
mentioning
confidence: 99%
“…Trignano et al [52] reported 100% healing and 0/8 recurrences of neuro-ischemic DFU at 18 months after ND.
Figure 3.A Kaplan Meier survival curve illustrates the ulcer-free survival of 42 cases with prior healed unilateral DFU and subsequent ND of that leg only. The previously intact contralateral leg, without ND, has a relative risk of subsequent ulceration of 5.5 ( p  = 0.048).
…”
Section: Objective Outcomesmentioning
confidence: 99%
“…Trignano et al [52] found 40 diabetic feet with ischemic levels of transcutaneous skin oxygenation (TcpO2) below 40 mm Hg had returned to levels above 40 after ND in 90% of cases by month 3 and 95% by 18 months. Nominal improvement occurred in 100%.…”
Section: Objective Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemia of the extremity as a result of atherosclerosis and diabetic vasculopathy, and diabetic peripheral neuropathy are main causes of diabetic foot ulcers . In various studies diabetic peripheral neuropathy is considered to be the main reason in the formation on diabetic foot ulcers …”
mentioning
confidence: 99%